Interstitial lung abnormalities in the Queensland Lung Cancer Screening Study: prevalence and progression over 2 years of surveillance. Issue 7 (11th July 2019) - Mackintosh, John A.; Marshall, Henry M.; Slaughter, Richard; Reddy, Taryn; Yang, Ian A.; Bowman, Rayleen V.; Fong, Kwun M.
Abstract: Background: We report the prevalence and progression of incidentally detected interstitial lung abnormalities (ILA) in the Queensland Lung Cancer Screening Study cohort. Methods: About 256 volunteers aged 60–74, with ≥30 pack years smoking history and forced expiratory volume in 1 s (FEV1) ≥50% predicted underwent low‐dose computed tomography (CT) chest screening. Electronic search of baseline (T0) and 2‐year follow‐up (T2) CT reports identified candidate cases using Fleischner Society interstitial terminology. Candidate CT were reviewed in a randomised order by two experienced radiologists and a senior respiratory medicine trainee blinded to the existing reports. Scans were evaluated for the presence and extent of ILA using an in‐house score, and graded for progression. Results: ILA were detected in 20/256 baseline cases (7.8%) with no incident cases detected at T2 surveillance imaging. Of these 20 cases, 9 (45%) had reticulation, 18 (90%) had ground glass change, 1 had traction bronchiectasis and 1 had randomly distributed nodularity. Seven cases with ground glass changes also had areas of reticulation, and only two had reticulation alone. All ILA were graded as minor except for traction bronchiectasis, which was moderate. Only one case progressed on T2 imaging. ILA were associated with the presence of auscultatory crackles (50% vs 11.6%, P = 0.001) and a lesser degree of emphysema (mean % volumetric emphysema 6.7% vs 9.8%, P = 0.009). No relationship was observed between baseline and serial lung function parameters. Conclusion: ILA are frequent incidental findings in lung cancer screening. In the majority of cases these abnormalities do not appear to change significantly over a 2‐year period of surveillance.